Goal‐directed Focused Ultrasound Milestones Revised: A Multiorganizational Consensus. (31st October 2016) - Nelson, Mathew; Abdi, Amin; Adhikari, Srikar; Boniface, Michael; Bramante, Robert M.; Egan, Daniel J.; Matthew Fields, J.; Leo, Megan M.; Liteplo, Andrew S.; Liu, Rachel; Nomura, Jason T.; Pigott, David C.; et al.
Abstract: In 2012 the Accreditation Council for Graduate Medical Education and the American Board of Emergency Medicine released the emergency medicine milestones. The Patient Care 12 (PC12) subcompetency delineates staged and progressive accomplishment in emergency ultrasound. While valuable as an initial framework for ultrasound resident education, there are limitations to PC12. This consensus paper provides a revised description of criteria to define the subcompetency. A multiorganizational task force was formed between the American College of Emergency Physicians Ultrasound Section, the Council of Emergency Medicine Residency Directors, and the Academy of Emergency Ultrasound of the Society for Academic Emergency Medicine. Representatives from each organization created this consensus document and revision.